Preventive Counselling Strategies for Enhancing Learning Concentration Among Students with Substance Use Challenges in Secondary Schools in Bokkos Local Government Area, Plateau State, Nigeria - Ibrahim, Solomon; David, Funmilayo Izams; Rachel , Funke Zedomi; Irene , Itse Jonah (Kashere Journal of Education, 2025)
This study investigated preventive counselling strategies for enhancing learning concentration among students with substance use challenges in secondary schools in the Bokkos Local Government Area, Plateau State, Nigeria. The study aimed to examine the extent to which preventive counselling interventions influence students’ focus in learning, identify the socio-cultural factors affecting their effectiveness, and assess the role of educational support in reinforcing these strategies. The study adopted a descriptive survey design, with a population of 96 students identified as experiencing substance use challenges. Data were collected using a structured questionnaire based on a four-point Likert scale and analysed using Pearson Product Moment Correlation to test the three hypotheses formulated. Findings revealed a significant positive relationship between preventive counselling strategies and students’ learning concentration, with socio-cultural factors and educational support further moderating this effect. The study concluded that structured, context-sensitive counselling interventions are effective in improving academic engagement among students with substance use challenges. It recommended the implementation of targeted counselling programmes, integration of socio-cultural considerations, regular awareness campaigns, collaboration with parents and community leaders, and the development of policies to institutionalise preventive counselling in secondary schools.